2018
DOI: 10.1111/bdi.12684
|View full text |Cite
|
Sign up to set email alerts
|

Increasing mortality gap for patients diagnosed with bipolar disorder—A nationwide study with 20 years of follow‐up

Abstract: The mortality gap between patients with bipolar disorder and the general Danish population has widened over the past two decades, which is a cause for concern, although reasons for the increasing mortality gap are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 34 publications
(50 reference statements)
3
44
0
Order By: Relevance
“…Despite differences between disorders there are similar patterns of increasing relative mortality rates over time for bipolar disorder and schizophrenia 2. Current data support the largest gap in mortality rate in younger persons with SMI as compared to the background population, as in this age group death is a relatively uncommon event in the general population 1. Over the last half a century, a significant increase in life expectancy has been observed, most likely as a result of earlier diagnosis and improved treatment for diseases eventually leading to death from natural causes.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Despite differences between disorders there are similar patterns of increasing relative mortality rates over time for bipolar disorder and schizophrenia 2. Current data support the largest gap in mortality rate in younger persons with SMI as compared to the background population, as in this age group death is a relatively uncommon event in the general population 1. Over the last half a century, a significant increase in life expectancy has been observed, most likely as a result of earlier diagnosis and improved treatment for diseases eventually leading to death from natural causes.…”
mentioning
confidence: 70%
“…If anyone dies—the question is when and what the cause is, and how the quality of life has been. Patients with bipolar disorder and patients with schizophrenia, most often comprising the group of patients defined as severe mental illness (SMI), have an increased mortality rate in comparison to the general population 1,2. Despite differences between disorders there are similar patterns of increasing relative mortality rates over time for bipolar disorder and schizophrenia 2.…”
mentioning
confidence: 99%
“…Life expectancies in populations of the European Union have been increasing over the last decades with a mean life expectancy of above 80 years. However, patients diagnosed with bipolar disorder have a reduced life expectancy of 8‐16 years as compared to the general population . In a Danish nationwide register‐based cohort follow‐up study, we showed that the mortality gap between patients with bipolar disorder and the general population has been increasing over the last 20 years .…”
mentioning
confidence: 88%
“…In general, the causes of years of life lost observed in patients with severe mental illness (SMI) are similar to those observed in the general population . Interventions aiming at reducing mortality and morbidity of somatic disorders have proven effective in the general population as indicated by the decreasing mortality rates, and these interventions would perhaps also be effective for somatic co‐morbidity in patients diagnosed with bipolar disorder …”
mentioning
confidence: 99%
See 1 more Smart Citation